A review on outcome-based education practices / Norlaila Abdullah - Abdullah, Norlaila (2013)
This review analysis involves the applications of an Outcome-Based Education (OBE) in a number of countries in Asia, United States of America, Australia and the Middle East. To address the goal of understanding OBE, the author turned to OBE practices of Lingnan University, Hong Kong. Using this as a base, the author has analyzed the critical success factors to support the modus operandi of a successful implementation of OBE. Issues relating to the intended learning outcomes, teaching and learning activities, outcome-based assessment and graduate attributes were the focal point of the discussion and used as indicators towards developing managerial accounting students cognitive, psychomotor and affective skills. In this context, OBE is proven to improve the quality of teaching and learning, competitiveness among graduates and students' English language proficiency. Consistent with this review, the study also include other countries' success and failure outcomes along with its rationale.